EKSPLORASI KONSEP NABAWI DALAM MENUMBUHKAN KEHARMONISAN RUMAH TANGGA POLIGAMI - Fahmi, Muhammad Nurul; Anas Burhanuddin; Abdul Rahman Ramadhan (Al-Majaalis : Jurnal Dirasat Islamiyah, 2024)
This research aims to analyse the concept applied by the Messenger of Allah -peace be upon him- in building polygamous household harmony. The polygamy law is a solution to various problems experienced by Muslims, especially Muslim women, as a form of uplifting women's dignity. The example shown by the Messenger of Allah -peace be upon him- and his companions as practitioners of the polygamy law is a depiction of the real and solutive implementation of polygamy initiated by Islam. However, the practice of unhealthy polygamy implemented by some groups under the pretext of implementing Islamic teachings today tends to prioritize prestige, pride, and lust. This is what makes the rejection and controversy related to polygamy even greater and wider. This is reinforced by the high divorce rate due to polygamy. This phenomenon is inversely proportional to the practice of polygamy in the life of the Messenger of Allah -peace be upon him- which was harmonious and peaceful, both the relationship between him as a husband with his wives and the relationship between the wives in polygamous life. This research is qualitative research with data collection using literature review techniques. The data used in this research comes from secondary data in the form of books, articles, and scientific journals that have information relevant to the research topic. This research uses content analysis as a data analysis technique and deductive concepts in making conclusions. The results of this research show that the concepts implemented by the Messenger of Allah -peace be upon him- in building the harmony of polygamous household life are fairness in the division of nights and provision, making the wives’ houses close to each other, visiting all wives every day, and gathering the wives in one house every night.